1995
DOI: 10.1111/j.1365-2249.1995.tb03863.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological distinction of integral plasma membrane proteins as a class of mycobacterial antigens and their relevance for human T cell activation

Abstract: SUMMARYThis study pertains to classification and antigenic analysis of mycobacterial plasma membrane proteins in relation to human T cell proliferativc responses, using a 'fast grower' Mycobacterium fortuitum as model. Membrane vesicles, prepared hy sonicalion and differential centrifugation, were subjected to biphasic Triton X-114 extraction for isolation of integral (detergent phase) and peripheral (aqueous phase) proteins. Neither protein pool showed any appreciable overlap serologically. SDS-PAGE showed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…The glycosylated constituents of MtM showed abundant binding to Con A, with a binding pattern similar to that reported in an earlier study [53]. Conspicuously, the low molecular mass (< 35 kDa) LAM moieties, which include LM and the membrane anchor PIMs [40,44,45] did not react with Con A suggesting that their mannose residues may be inaccessible to the lectin. Additionally, Con A did not stain any of the major MtM-SMALP proteins.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The glycosylated constituents of MtM showed abundant binding to Con A, with a binding pattern similar to that reported in an earlier study [53]. Conspicuously, the low molecular mass (< 35 kDa) LAM moieties, which include LM and the membrane anchor PIMs [40,44,45] did not react with Con A suggesting that their mannose residues may be inaccessible to the lectin. Additionally, Con A did not stain any of the major MtM-SMALP proteins.…”
Section: Discussionsupporting
confidence: 82%
“…The TEM image of MtM showed clusters of vesicles formed spontaneously in the aqueous medium. Formation of such vesicles, typical of a plasma membrane, was also reported by us for a 'fast-grower' mycobacterium-M. fortuitum [45] and by Chiaradia et al [46] for another fast-grower, M. smegmatis. In the latter study, it was also shown that the mycobacterial outer membrane appears as 'unclosed' fragments suggesting that our MtM preparation represented the plasma (or inner) membrane of Mtb.…”
Section: Discussionsupporting
confidence: 74%
“…LMG lists among the most malignant ulcers and may occur as a granulomatous response of microbial etiology ( 5 – 8 ). Staphyloccus aureus ( 30 ), Nocardia farcinica ( 31 ), Mycobacterium fortuitum, M. marinum ( 32 ), Leishmania infantum ( 33 ), and EBV ( 9 – 11 , 34 ) are among the suspected causative agents. Mucoralean fungi have been reported to cause infections with highly similar clinical features ( 1 , 24 – 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported the inducement of proliferation in ENKTL-NT patients with M. irregularis or R. arrhizus infection ( 16) (Figures 7-9). We retrieved, from the peers, a series of reports about the proliferation of cytotoxic T lymphocytes induced by Staphyloccus aureus (125), Nocardia farcinica (126), Mycobacterium fortuitum, M. marinum (127), and Leishmania infantum (128), all of which were reported to induce ENKTL-NT-like syndrome (129-132). Still, another research reported the recovery of ENKTL-NT following treatment with sulfamethoxazole and levofloxacin when the infections were confirmed in the blood cultures (133).…”
Section: Atypical Hyperplasia With Ki-67 Expressionmentioning
confidence: 99%